MILK AGGRAVATES ASTHMA – THE TRUTH OR THE PERCEPTION - Muhammad Khalid Azam Khan (Army Medical College Rawalpindi, 2020)
Objective: To assess the notion that milk can cause or aggravate asthma and break this myth.